Design of Smart Parking System Using Ultrasonic Sensor to Optimize Parking Lots On Campus - Lubis, Faisal; Sundawa, Bakti Viyata; Cholish, Cholish; Abdullah, Abdullah (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
Monitoring the availability of parking lots in the campus area is very important. This is related to the solution of the problem of limited parking spaces for four-wheeled vehicles. Existing parking spaces can be optimized by adding a vehicle detection device. This vehicle detection device uses ultrasonic sensors and its programming is based on the ESP32 Microcontroller. Sensitivity parameters measured are object detection distance, influence of other frequencies, influence of passing objects and range areas horizontally and vertically. In the research, the measurement results obtained are object detection distance up to 350 cm, the influence of other frequencies does not exist, passing objects can be detected by vehicle detection devices, range areas vertically up to 250 cm and horizontally up to 150 cm. Based on the test results, the distance reading by the ultrasonic sensor on the vehicle detection device is accurate. This measurement is in accordance with the specifications of the GH-311 type ultrasonic sensor used in the device.